2021
DOI: 10.1080/2162402x.2021.1938475
|View full text |Cite
|
Sign up to set email alerts
|

Immune-checkpoint blockade of CTLA-4 (CD152) in antigen-specific human T-cell responses differs profoundly between neonates, children, and adults

Abstract: 2021) Immune-checkpoint blockade of CTLA-4 (CD152) in antigen-specific human T-cell responses differs profoundly between neonates,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…2c , Table S7 ) was detectable in all S. aureus stimulated T-cells. In extension to a published study of total CD4 + T-cells 3 , experiments were performed using naïve T-cells. The accumulation/secretion of IFN-γ was three times higher in supernatants of S. aureus -simulated T-cells of donors being 6 years and older compared to 0–5-year-olds (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2c , Table S7 ) was detectable in all S. aureus stimulated T-cells. In extension to a published study of total CD4 + T-cells 3 , experiments were performed using naïve T-cells. The accumulation/secretion of IFN-γ was three times higher in supernatants of S. aureus -simulated T-cells of donors being 6 years and older compared to 0–5-year-olds (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A child faces the greatest probability of dying within the first 28 days after birth, followed by the first 5 years of life 1 , 2 . Although studies have shown that the immune system early in life reacts differently compared to that of adults, the developmental-specific mechanisms of triggering an antibacterial response and avoiding an adverse reaction are yet not completely understood 3 7 . Recently, a predetermined developmental trajectory of the composition of the cell populations in blood during the first 3 months of life was reported; however, data thereafter and functional characteristics of these cells are not addressed in depth 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…To specifically compare the properties of antigen-inexperienced CD4 T-cells, the naïve (CD45RA) CD25 neg CD4 T-cells of neonates (nT N ) and adults (T N ) were enriched in addition to the memory (CD45RO) CD25 neg CD4 T-cells (T M ) using MACS [ 14 ]. The enriched CD4 T-cells were treated with PD-1- and PD-L1-blocking antibodies or isotype controls and were either allowed to rest or stimulated with SEB or with S. aureus -loaded autologous monocytes and analyzed 3 and 5 days after the onset of stimulation, respectively ( Figure 1 a) [ 21 , 25 ]. An up-regulation of the TCR-signaling induced surface molecule CD69 was monitored upon the SEB and S. aureus encounter but not in the resting conditions of co-cultures of CD4 T-cells with unloaded monocytes ( Figure 1 b,c).…”
Section: Resultsmentioning
confidence: 99%
“…The monocytes were matured with h.i. S. aureus with no expression of the Staphylococcal enterotoxin B (SEB neg ) [ 25 ]. In brief, the monocytes were pulsed with 10 µg/mL S. aureus in a complete RPMI1640 medium (PAN BioTech) for 24 h at 37 °C/5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation